Employees Usage Of Communication Technology During Non-Work Hours: A Study On Higher Educational Institutions In Malaysia - Ahasanul Haque, Naila Anwar, Arun Kumar Tarofder, Ferdous Azam (International Journal of Advanced Science and Technology, 2020)
today’s technology-driven world, an understanding regarding the use of communicationtechnology has emerged as a crucial aspect. Therefore, this study took the initiative of comprehendingthis phenomenon in the context of the education sector, particularly in the Malaysian setting. Thepopulation consists of employees working in the different educational institutions in Malaysia. Arandom sampling method was used for the purpose of collecting the required data. The sample size ofthe study was 221. Later, the structural model was verified and the hypotheses were tested throughSEM. The results of the study have unveiled that several aspects, specifically job engagement, jobsatisfaction and life satisfaction are favourably associated to each other and in turn, job satisfactionshares a meaningful relationship with the usage of communication technology. Therefore, it can beconcluded that the more employees are engaged and satisfied with their job the higher is theirsatisfaction level with their lives. Finally, this study suggests that the current model can be furtherdeveloped through the integration of additional relevant constructs.